Effects of Robot-assisted Gait With Body Weight Support on Torque, Work, and Power of Quadriceps and Hamstring Muscles in Healthy Subjects - Jihun Hwang; Sung (Joshua); Woochol Joseph Choi; Chung-hwi Yi (Korean Research Society of Physical Therapy, 2021)
Background: Robot-assisted gait training (RAGT) is an effective method for walking rehabilitation. Additionally, the body weight support (BWS) system reduces muscle fatigue while walking. However, no previous studies have investigated the effects of RAGT with BWS on isokinetic strength of quadriceps and hamstring muscles. Objects: The purpose of this study was to investigate the effects of torque, work, and power on the quadriceps and hamstring muscles during RAGT, using the BWS of three conditions in healthy subjects. The three different BWS conditions were BWS 50%, BWS 20%, and full weight bearing (FWB). Methods: Eleven healthy subjects (7 males and 4 females) participated in this study. The Walkbot_S was used to cause fatigue of the quadriceps and hamstring muscles and the Biodex Systems 4 Pro was used to measure the isokinetic torque, work, and power of them. After RAGT trials of each of the three conditions, the subjects performed isokinetic concentric knee flexion and extension, five at an angular velocity of 60°/s and fifteen at an angular velocity of 180°/s. One-way repeated analysis of variance was used to determine significant differences in all the variables. The least significant difference test was used for post-hoc analysis. Results: On both sides, there were significant differences in peak torque (PT) of knee extension and flexion between the three BWS conditions at an angular velocity of 60°/s and 180°/s conditions. A post-hoc comparison revealed that the PT in the BWS 50% was significantly greater than in the BWS 20% and the FWB and the PT in the BWS 20% was significantly greater than in the FWB. Conclusion: The results of this study suggest that the lower BWS during RAGT seems to lower the isokinetic torque, work, and power of the quadriceps and hamstring muscles because of the muscle fatigue increase.